2022
DOI: 10.3390/ijerph19042229
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome in a Military Tertiary Hospital Staff during the COVID-19 Contingency

Abstract: (1) Background: Burnout syndrome (BOS) is defined as a psychological state of physical and mental fatigue associated with work. The COVID-19 pandemic greatly impacted the physical and mental wellbeing of health professionals. The objective of this work was to determine the impact on personnel, monitoring the frequency of BOS throughout the pandemic. (2) Methods: The Maslach Burnout Inventory (MBI) was self-applied in four periods of the pandemic according to sociodemographic and employment characteristics. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
3
8
1
2
Order By: Relevance
“…In addition, military personnel with fear of COVID-19 significantly increased the prevalence of emotional exhaustion. This is similar to that reported by Martinez-Cuazitl et al who reported 32.9% emotional exhaustion in military personnel [ 15 ]. Additionally, other studies found 35.7% with moderate and 31.9% with severe emotional exhaustion, being the main predictors of this condition the working hours, psychological comorbidities, and fear of infection [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, military personnel with fear of COVID-19 significantly increased the prevalence of emotional exhaustion. This is similar to that reported by Martinez-Cuazitl et al who reported 32.9% emotional exhaustion in military personnel [ 15 ]. Additionally, other studies found 35.7% with moderate and 31.9% with severe emotional exhaustion, being the main predictors of this condition the working hours, psychological comorbidities, and fear of infection [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…Depersonalization is defined as a distant or indifferent attitude towards work, which manifests itself as insensitive and cynical behavior. The result found in this study is higher than that reported by a study in Mexico where 30.7% were found in the military [ 15 ]. Additionally, it differs from that found in European studies with a prevalence of 58.0% [ 11 ].…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations